Fluorine‐Free Slippery Liquid‐Infused Porous Surfaces Prepared Using Hierarchically Porous Aluminum. Issue 13 (20th January 2020) - Inoue, Tomohiro; Koyama, Akira; Kowalski, Damian; Zhu, Chunyu; Aoki, Yoshitaka; Habazaki, Hiroki
Abstract : Slippery liquid‐infused porous surfaces (SLIPS) have been receiving increased attention. Fluorinated compounds have been used to prepare SLIPS, but because of bioaccumulation and ecological impact of perfluoroalkyl building blocks, the fluorine‐free SLIPS (F‐free SLIPS) system is preferable for practical applications. Herein, SLIPS are prepared from a hierarchically porous aluminum substrate, tetradecylphosphonic acid monolayer coating, and silicone lubricant oil. The several properties of the SLIPS, including durability against lubricant loss, ice adhesion, and corrosion resistance, are compared with those with a fluoroalkyl monolayer coating and fluorinated lubricant oil. The findings demonstrate that the F‐free SLIPS show higher durability against the removal of lubricant in air and also in water. Both fluorinated SLIPS (F‐SLIPS) and F‐free SLIPS samples exhibit extremely reduced ice adhesion compared with superhydrophobic surfaces obtained using the same hierarchically porous aluminum substrate with fluorinated or fluorine‐free monolayer coating. The SLIPS samples have very high corrosion resistance in NaCl solution but not in alkaline solution. The solution‐dependent corrosion resistance is discussed in terms of the stability of monolayer coating. Abstract : Fluorine‐free slippery liquid‐infused porous aluminum surfaces with silicone oil lubricants are prepared in this study. The low ice adhesion strength and high corrosion resistance in HCl and NaCl aqueous solutions of the fluorine‐free aluminum samples are revealed, and the better lubricant retention of the fluorine‐free samples compared with the fluorinated ones is also found herein.